Penetapan Kadar Hidrokortison Asetat dalam Sediaan Krim Mengandung Pengawet Nipagin secara Spektrofotometri Derivatif Orde Pertama - Hayun, Hayun; Leswara, Nelly D.; Zarkasih, Lutfhi (UI Scholars Hub, 2014)
The simple and rapid spectrophotometric methods were developed for analysis of hydrocortisone acetate in cream pharmaceutical formulations containing nipagin as preservative. Concentration of hydrocortisone acetate was determined by measuring the first derivative absorption (ratio amplitudes) at 257.0 nm (zero crossing for nipagin). The calibration graphs were linear over the range of 4.0-40.0 ppm of hydrocortisone acetate (r= 0.9999). The limit of detection (LOD) and the limit of quantitation (LOQ) were found to be 0.9617 ppm and 3.2050 ppm, respectively. This method had good precision (repeatability and intermediate precision) with RSD < 2.0% where as the means of the recovery data (accuracy) were 102.03±0.14% and 100.23±0.69% for hydrocortisone acetate cream 1% and 2.5%, respectively. The proposed method was applied for the determination of hydrocortisone acetate in three out of four commercial cream formulations samples and the results of label claim were 102.93±0.22%, 108.48±0.19% and 106.67±0.35% for sample A, B and D, respectively. The result of brand C analysis showed to contain more than 110.0% of the labeled amount of hydrocortisone acetate, indicated there was additive other than nipagin in the cream basis to interfer with the hydrocortisone acetate measurements.